Analysis of Phytochemical Constituents and Biological Activity of Taxus Wallichiana Zucc. Dolakha District of Nepal - Subba, Bimala (International Journal of Applied Sciences and Biotechnology, 2018)
Phytochemical and biological activities of methanolic extract of Taxus wallichiana Zucc. (Leaf, stem) were carried out. The brine shrimp bioassay showed T. wallichiana is pharmacologically active. The antibacterial potential was studied against one gram positive bacteria (Staphylococcus aureus) and one gram negative bacteria (Escherichia Coli) using Agar Well Diffusion Method. Stem of T. wallichiana showed significant zone of inhibition against gram positive bacteria while the leaf of T. wallichiana did not show significant zone of inhibition against both gram positive and gram negative bacteria. Antioxidant activity was evaluated by 2, 2-diphenyl-1-picryl hydrazyl (DPPH) free radical scavenging activity and FRAP assay. Both assay showed that T. wallichiana leaves has high antioxidant activities. Int. J. Appl. Sci. Biotechnol. Vol 6(2): 110-114